Four-Year Longitudinal Study of Motor and Non-motor Symptoms in LRRK2-Related Parkinson's Disease - Xiao Deng; Bin Xiao; Hui-Hua Li; Ebonne Ng; Yew-Long Lo; Yew-Long Lo; Eng-King Tan; Eng-King Tan; Kumar M. Prakash; Kumar M. Prakash (Frontiers in Neurology, 2020)
Objectives: In a prospective 4-year study, we evaluated the progression of motor and non-motor symptoms in Parkinson's disease (PD) patients with Asian-specific LRRK2 risk variants and non-carriers.Methods: A total of 202 patients with PD, including 133 risk variant carriers and 69 non-carriers, were followed up and evaluated using the Modified Hoehn and Yahr staging scale, Unified Parkinson's Disease Rating Scale part III, Non-motor Symptom Scale, Parkinson's disease Questionnaire-39 item version. Means of generalized estimating equation model was performed to compare the differences from baseline between LRRK2 risk variant carriers and non-carriers.Results: Our longitudinal analysis revealed that risk variant carriers exhibited greater progression than non-carriers after 4 years based on the modified Hoehn and Yahr staging scale (risk variants carriers, 0.65; non-carriers, 0.06; P = 0.041). Meanwhile, Unified Parkinson's Disease Rating Scale gait and posture score in risk variant carriers also showed greater increase than that in non-carriers, although the difference was not statistically significant. Non-carriers experienced a transient improvement in non-motor symptoms at the early stage of PD, as scores at visit two significantly reduced compared to baseline in Non-motor Symptom Scale domain 3 (mood/apathy), Parkinson's disease Questionnaire-39 item version domain 3 (emotional well-being), and frequency of NMS in non-carriers but not in risk variants carriers.Conclusions: PD gene risk variant carriers were more likely to progress faster in their motor severity than non-carriers. There were transient differences in certain non-motor symptoms and quality of life in carriers. However, more studies are warranted to assess the association of PD risk variants and progression of non-motor symptoms.